Effectiveness of Deproteinized Bovine Bone in Maxillary Sinus Bone Regeneration: A Systematic Review and Descriptive Synthesis of Histological Evidence - Urbizo Vélez, Joaquín Juan (2025)
Surgical maxillary sinus lifting for the placement of dental implants is a widely used procedure. A crucial step in these maneuvers is the placement of grafts to facilitate the rapid regeneration of bone tissue and achieving a base for implants osseointegration.  To evaluate the histological and histomorphometric outcomes of maxillary sinus floor elevation procedures performed with deproteinized bovine bone, synthesizing the available evidence on its regenerative effectiveness. This systematic review, following PRISMA guidelines, analyzed studies from November 2024 to February 2025 on maxillary sinus floor elevation using deproteinized bovine bone. Using the PICO framework, it focused on histological bone regeneration outcomes. Searches in PubMed, Scopus, Web of Science, and grey literature were screened by two reviewers, with bias assessed using Cochrane’s RoB 2 and ROBINS-I  tools. Fourteen studies were included. All RCTs and NRS showed low risk of bias. Bone formation ranged from 17.3% (Bio-Oss®) to 80.8% (SmartBone®). Combined grafts with BMAC or Emdogain® enhanced outcomes. Within the limitations of the current evidence, Bio-Oss and HA-TCP appear to be viable options for maxillary sinus bone regeneration, though differences exist in resorption rates and bone formation properties. Due to study heterogeneity, unequal group sizes, and risk of bias, the certainty of these findings is low, and further robust long-term trials are required.